IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN OGAN KOMERING ULU - Novia Kencana (Jurnal Pemerintahan dan Politik, 2019)
The purpose of this study was to present the results of  recycle trash implementation policy in Ogan Komering Ulu District based on Regulation number 5 year 2009 about recycle trash and constraints faced in recycle trash implementation policy in Ogan Komering Ulu District. This study used qualitative research method and the technique of collecting data through interview, observation and documentation. This study used a model or policy implementation approach of George C. Edward III, namely communication, human resources, disposition and bureaucracy structure to see and know the recycle trash policy implementation in Ogan Komering Ulu District.The results showed that the  recycle trash implementation policy in Ogan Komering Ulu District based on Regulation Ogan Komering Ulu district number 5 year 2009 about trash recylce in general were running well, but not optimal. It was because many obstacles that interfere the process of implementation of the policy, namely participation or society awareness who did not really support government policy. Facilities and infrastructure are inadequate and limited budgets by Departement of Hygine and Town Beauty Kota Ogan Komering Ulu made yet optimal implementation of this trash of public service fields.Keyword: Implementation, Policy, Trash Recycle